Regulation of CK2 by Phosphorylation and O-GlcNAcylation Revealed by Semisynthesis - Tarrant, Mary Katherine (2012)
Protein Ser/Thr kinase CK2 (casein kinase II) is involved in a myriad of cellular processes including cell growth and proliferation by phosphorylating hundreds of substrates, yet the regulation process of CK2 function is poorly understood. Here we report that the CK2 catalytic subunit CK2α is modified by O-GlcNAc on Ser347, proximal to a cyclin-dependent kinase phosphorylation site (Thr344) on the same protein. We use protein semisynthesis to show that Thr344 phosphorylation increases CK2α cellular stability via Pin1 interaction whereas Ser347 glycosylation appears to be antagonistic to Thr344 phosphorylation and permissive to proteasomal degradation. By performing kinase assays with the site-specifically modified phospho- and glyco-modified CK2α in combination with CK2β and Pin1 binding partners on human protein microarrays, we show that CK2 kinase substrate selectivity is modulated by these specific posttranslational modifications. This study suggests how a promiscuous protein kinase can be regulated at multiple levels to achieve particular biological outputs.